Influence of the Preparation "Nicavet-1000" on a Morphofunctional Condition of some Organs of Rats at Experimental Aluminium Intoxication - David A. Areshidze; Lyudmila D. Timchenko; Igor V. Rzhepakovsky; Maria A. Kozlova; Iaroslavna A. Kusnetsova; Ivan A. Syomin (Journal of Pharmacy and Nutrition Sciences, 2017)
During the conducted research, it is established that aluminium chloride intoxication leads to the considerable changes of composition of red blood, development of a hypercalcemia and change of a bone structure of animals. A number of significant morphofunctional changes in the hippocampus of the examined animals are also noted. The use of the tissue preparation "Nicavet-1000" leads to the normalization of both hematocrit and other parameters of red blood, as well as to the intensification of erythropoiesis. Use of the preparation "Nicavet-1000", judging from the results of research, prevents pathological changes in a bone tissue, caused by aluminium chloride. "Nicavet-1000" leads to the expressed normalization of both the morphological, and micromorphometric parameters characterizing a hippocampus of rats.